Cytisus multiflorus: phenolic characterization by HPLC-DAD, ESI-MSn and NMR combined methods - Pereira, Olívia R. (2012)
Cytisus multiflorus is a well known Mediterranean plant presenting diuretic, anti-inflammatory, anti-hypertension and antidiabetic properties [1]. The high phenolic content of C. multiflorus is frequently associated to its health beneficial properties, however its phenolic composition remains unclear. In this work, the phenolic profile of an extract of C. multiflorus flowers was elucidated. After extraction with an aqueous ethanolic solution (80%), the enrich phenolic extract was analyzed by high performance liquid chromatography with diode array detection, electrospray mass spectrometry [2] and nuclear magnetic resonance techniques. The extract of C. multiflorus was mainly composed with chrysin-7-O-β-D-glycopyranoside (MW 416) that accounted for 15.9±2.3 mg/g of dried plant. It also contained considerable amounts of rutin (4.5±0.7 mg/g), a dihydroxyflavone isomer of chrysin (7.0±1.3 mg/g), 2′′-O-pentosyl-6-C-hexosyl-luteolin (3.3±0.5 mg/g), 2′′-O-pentosyl-8-C-hexosyl-luteolin (3.5 ± 0.3 mg/g) and 6′′-O-(3-hydroxy-3-methylglutaroyl)-2′′-O-pentosyl-C-hexosyl-apigenin (3.6±0.7 mg/g), which are not commonly found in the Fabaceae family. Other unusual phenolic compounds found in minor amounts in the ethanolic extract of C. multiflorus flowers comprised the flavones 2′′-O-pentosyl-6-C-hexosyl-apigenin, 2′′-O-pentosyl-8-C-hexosyl-apigenin and 6′′-O-(3-hydroxy-3-methylglutaroyl)-2′′-O-pentosyl-C-hexosyl-luteolin. The present work emerges as an important contribution for the phenolic characterization of Cytisus genus and of Fabaceae family.